2014
DOI: 10.7860/jcdr/2014/8560.4470
|View full text |Cite
|
Sign up to set email alerts
|

Grading of Extraction and Its Relationship with Post-operative Pain and Trismus, along with Proposed Grading for Trismus

Abstract: IntrOductIOnExtraction of mandibular third molar is a common practice in dentistry. As mandibular third molar is the last tooth to erupt, due to reduced space between mandibular second molar and ramus of mandible, most of the times it is malaligned, impacted, with hooked or curved root. Mandibular third molar's proximity to inferior alveolar canal, position of external oblique ridge as well as impaction status make its extraction more venerable for post-operative complications [1] like pain, swelling and trism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Those authors also observed more accidents and complications relative to the complexity of surgical procedures. Other studies show the post-operative morbidity increase with longer procedures 19 . This study found no relationship between complications and surgical time.…”
Section: Discussionmentioning
confidence: 89%
“…Those authors also observed more accidents and complications relative to the complexity of surgical procedures. Other studies show the post-operative morbidity increase with longer procedures 19 . This study found no relationship between complications and surgical time.…”
Section: Discussionmentioning
confidence: 89%
“…If there is an increased risk of postoperative complications, telemedical follow-up alone should be questioned on the basis of current data. Risk groups include patients with acute and/or chronic infections in the surgical area [ 45 , 46 , 47 ], higher age [ 40 , 47 , 48 , 49 ], incompliance [ 47 ], impacted teeth [ 45 , 46 , 50 , 51 , 52 ], poor oral hygiene [ 45 , 53 ], systemic diseases affecting wound healing (chronic renal or liver diseases, diabetes mellitus, immunosuppression, malnutrition) [ 47 , 54 ], prolonged operation time [ 43 , 48 , 49 , 51 ], history of radiation, chemotherapy or antiresorptive medication [ 47 , 55 ], bleeding disorders (e.g., hemophilia, thrombocytopenia), antiplatelet therapy or anticoagulation [ 55 ], and habits such as smoking and drinking [ 47 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…A facial swelling assessment was performed using the methodology of Gabka and Matsumura 23 (Figure 1). The degree of mandible postoperative contracture, measured as an interincisal distance by maximal mouth opening, was determined as I degree when 1%−33% limitation in mouth opening was registered; II degree—34%–66%, and III degree—from 66% to 100% 24 . The postoperative pain intensity was registered using a visual analog scale, as follows: 1–4 mm, mild pain; 5–7 mm, moderate pain; 8–10 mm, severe pain 21 …”
Section: Methodsmentioning
confidence: 99%
“…The degree of mandible postoperative contracture, measured as an interincisal distance by maximal mouth opening, was determined as I degree when 1%−33% limitation in mouth opening was registered; II degree-34%-66%, and III degree-from 66% to 100%. 24 The postoperative pain intensity was registered using a visual analog scale, as follows: 1-4 mm, mild pain; 5-7 mm, moderate pain; 8-10 mm, severe pain. 21 In all mandibular third molar extractions, an equal standard protocol was performed by the same oral surgeon.…”
Section: Participants and Interventionmentioning
confidence: 99%